2022
DOI: 10.3389/fphar.2022.908212
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects and Safety of Dexmedetomidine Added to Nalbuphine or Sufentanil Patient-Controlled Intravenous Analgesia for Children After Tonsillectomy Adenoidectomy

Abstract: Tonsillectomy is a frequently performed surgical procedure in children, requiring post-operative analgesia. This study evaluated the efficacy and safety of nalbuphine or sufentanil combined with dexmedetomidine for patient-controlled intravenous analgesia (PCIA) after pediatric tonsillectomy adenoidectomy. A total of 400 patients undergoing tonsillectomy with and without adenoidectomy were included in the study. Patients received a PCIA pump (0.5 mg/kg nalbuphine, 2 μg/kg dexmedetomidine and 0.9% sodium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…29 A previous research demonstrated that DEX added to NAL PCIA enhanced the analgesic effects, attenuated the postoperative pain, and reduced the stress response after pediatric tonsillectomy adenoidectomy. 30 The analgesic potency of SUF to NAL can be considered to be 1:1000, suggesting 1 μg SUF was considered to be equivalent to 1 mg NAL, which has been compared with several previous studies. For example, NAL at 0.128 mg/ kg used in outpatient-induced abortion as an intraoperative and postoperative analgesic showed a better effect compared with equivalent dose of SUF (0.128 μg/kg).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…29 A previous research demonstrated that DEX added to NAL PCIA enhanced the analgesic effects, attenuated the postoperative pain, and reduced the stress response after pediatric tonsillectomy adenoidectomy. 30 The analgesic potency of SUF to NAL can be considered to be 1:1000, suggesting 1 μg SUF was considered to be equivalent to 1 mg NAL, which has been compared with several previous studies. For example, NAL at 0.128 mg/ kg used in outpatient-induced abortion as an intraoperative and postoperative analgesic showed a better effect compared with equivalent dose of SUF (0.128 μg/kg).…”
Section: Discussionmentioning
confidence: 94%
“…Recently, NAL considered to be a more ideal and safer analgesic, and it has been widely used in pediatric and gynecological surgery, with a ceiling effect on respiratory depression 29 . A previous research demonstrated that DEX added to NAL PCIA enhanced the analgesic effects, attenuated the postoperative pain, and reduced the stress response after pediatric tonsillectomy adenoidectomy 30 . The analgesic potency of SUF to NAL can be considered to be 1:1000, suggesting 1 μg SUF was considered to be equivalent to 1 mg NAL, which has been compared with several previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative analgesia with intravenous nalbuphine is common in children undergoing tonsillectomy and adenoidectomy [10][11][12], but its application in cleft palate repair is rarely reported. The purpose of this study was to observe the effect of different doses of nalbuphine on postoperative intravenous analgesia in children with cleft palate.…”
Section: Introductionmentioning
confidence: 99%